Impact of branding and product augmentation on decision making in the B2B market - N. S. Alexander; G. Bick; R. Abratt; M. Bendixen (South African Journal of Business Management, 2009)
The aim of this study was to investigate the impact of the brand and product augmentation on the buyers of industrial tyres. While much has been studied about branding Issues in B2C markets, very little research has been conducted in B2B markets. The research method used was a conjoint analysis experiment. The subjects were decision-making unit (DMU) members of open-pit mining companies in South Africa who purchased industrial tyres for mining operations. The results suggest that the brand is very important, followed by durability, and price. Differences of magnitude amongst the members of the DMU occurred. The impact of these findings as well as the implications for buyers and suppliers are discussed.
Keywords: 650